Public and Private Regimes in the Telecommunications Sector: A Study on one Difference and one Similarity - Quinalia, Cristiana Leão (Law, State and Telecommunications Review, 2015)
Purpose ”“ This article aims to analyze the characteristics of public and private regimes established in Brazil’s General Telecommunications Law (LGT), outlining specificities and connections between them. The categorization of telecommunications services and universal deployment of services were elected in this study, respectively, as a possible difference and similarity between the regimes. Methodology/approach/design ”“ So as to analyze differences between public and private regimes described in LGT, this article tackled the building blocks of each regime, particularly from the viewpoint of articles 21 and 175 of the Brazilian Constitution of 1988 and the legal framework inaugurated with LGT. To that end this study focused and deepened the legal bases and mechanisms in both public and private regimes. Findings ”“ In light of this analysis, it is adopted the view that only on the public regime the provision of telecommunications services is considered public service. Still, it is possible to identify elements of connection between the two regimes, notably the fact that both are targeted for policy-oriented expansion. Practical implications ”“ The understanding of differences and similarities between the regimes provide grounds for improving public policies and regulations.